GPRS Radio Communication For AI-Based Measurement And Control Complex - Bayramov, Azad; Suleymanov, Samir (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This paper presents the results of development of the GPRS radio communication modem for an autonomous measurement and control complex based on Artificial Intelligence. The complex is designed for simultaneous measurement of the concentration level of radioactive radon gas in the near-surface layer, the level of the Earth's magnetic field intensity with simultaneous analysis of seismic processes in the territory of Azerbaijan and neighboring regions. while measuring the magnetic field strength, solar activity is simultaneously analyzed. GPRS radio communication modem was developed to ensure communication with the Internet, to apply the machine learning method and communicate with the center. The purpose of the development and research is to study the correlations of measured values ​​with seismic activity. A software algorithm has been developed to control the complex and carry out measurements.